El programa aprendiendo en movimiento y su importancia en el proceso de enseñanza y aprendizaje, en niños y niñas de educación inicial ii de la unidad educativa Ramón Páez de la parroquia Eloy Alfaro cantón Latacunga provincia de Cotopaxi barrio Patután en el año lectivo 2014- 2015 - Guanoluisa Aquieta, Silvia Elizabeth (2015)
The research was conducted based on verified facts that were to reveal the lack of physical activity in class hours becoming boring and distracting them from learning easily, which is why the Learning in Motion program which links physical activity and good nutrition for created so get a good learning game-just as the working method was included in order to develop their motor skills so that they have no difficulty doing the activities that the teacher asks. To verify that need to be implemented within the initial education curriculum program research was carried out at the authorities, teachers ranging from pre and parents about the methods used in class and power they are providing them at home is why it was decided to create a guide that will benefit teachers and parents which consists of nutritious food and fun accompanied by age-appropriate activities and rescuing traditional games, it helps more teachers ranging from pre take account of this program and to implement so are mediating the development of skills and abilities of the boy and girl.